Immunological markers of anti-tumor dendritic cells vaccine efficiency in patients with non-small cell lung cancer - Skachkova, O.V.; Khranovska, N.M.; Gorbach, O.I.; Svergun, N.M.; Sydor, R.I.; Nikulina, V.V. (Experimental Oncology, 2013)
Aim - to investigate the quantitative and functional status of peripheral blood lymphocytes in patients with non-small cell lung cancer during DC-vaccine therapy and identify the most informative immunological parameters which are associated with clinical outcome. The study was conducted within the framework of randomized phase III clinical trial of DC-vaccine efficacy in patients with non-small cell lung cancer. Quantitative composition of peripheral blood lymphocytes was determined by flow cytometry. Cytokines mRNA expression level was estimated using real-time RT-PCR. In our study the most pronounced changes in the immune system have been defined after fourth DC-vaccine injection. Immunologic features such as reduction the MIP-1 alpha mRNA expression level, increasing the RANTES mRNA expression level and NK-cells count, retention CD4/CD8 ratio at physiological level were associated with favorable clinical outcome after DC-immunotherapy. Conclusions: immunological markers established in our investigation can be used for estimation of DC-immunotherapy efficiency. The results of our research are very promising, but these data should be confirmed in further studies with a large cohort of patients. Key Words: lung cancer, DC-vaccine, immunological monitoring, effector cells, chemokines.